2019
DOI: 10.5539/jas.v11n17p35
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Growth and the Yield of Eggplant Crop Under Different Irrigation Depths and Magnetic Treatment of Water

Abstract: The use of magnetizers for the treatment of irrigation water can be used in agriculture as an alternative to increase the growth and yield of several crops. The objective of this study was to evaluate the effect of different irrigation depths and magnetic treatment of water on eggplant crop cultivated in protected environment. The study was carried out in two experiments, in the first one, the design was completely randomized with four replications and two factors: water depths (50, 75 and 100% ETc) for two wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
3
2
0
Order By: Relevance
“…For the RDM variable, there was no significant difference between the water replacement depths of 75 and 100% ETc, however, when compared to the water replacement depth of 50% ETc, a significant difference was found. In an experiment conducted by Souza et al (2019), eggplant plants cultivated with 100% ETc had a higher accumulation of stem and leaf dry matter, similar to the results found in the present study.…”
Section: Resultssupporting
confidence: 90%
“…For the RDM variable, there was no significant difference between the water replacement depths of 75 and 100% ETc, however, when compared to the water replacement depth of 50% ETc, a significant difference was found. In an experiment conducted by Souza et al (2019), eggplant plants cultivated with 100% ETc had a higher accumulation of stem and leaf dry matter, similar to the results found in the present study.…”
Section: Resultssupporting
confidence: 90%
“…In the second experiment, the YLD of bell pepper with a depth of 100% ETc was 2939.4 g per plant, higher than the depth based on 75% ETc, with YLD equal to 2516.8 g per plant, an increase of 16.8%. Thus, as observed in this study, water deficit caused a restriction in eggplant yield, independently from the water treatment used, with lower values for the variables studied than the hydric supplementation with 100% ETc (Souza et al, 2019). Similar results of Souza et al (2019) were found by Seron et al (2019) for scarlet eggplant cultivation.…”
Section: Resultssupporting
confidence: 82%
“…Thus, as observed in this study, water deficit caused a restriction in eggplant yield, independently from the water treatment used, with lower values for the variables studied than the hydric supplementation with 100% ETc (Souza et al, 2019). Similar results of Souza et al (2019) were found by Seron et al (2019) for scarlet eggplant cultivation. The authors did not observe significant responses between the water treatment and the ETc levels evaluated.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Several studies aim to understand the mechanisms of using water treated with magnetic fields [27,32]. For Populus [33], eggplant [34], wheat [35], and lettuce crops [36], it was found that it provided a reduction in the effects caused by water stress conditions. In addition, studies with germination in tomatoes [37,38] and wheat [39] in saline conditions showed greater development when irrigated with treated water.…”
Section: Introductionmentioning
confidence: 99%